SOCIAL AND PSYCHOLOGICAL MANIFESTATIONS OF PROFESSIONAL IDENTITY CRISIS OF LABOR MIGRANTS - Blynova, Olena; Chervinska, Inna; Kazibekova, Viktoriia; Bokshan, Halyna; Yakovleva, Svitlana; Zaverukha, Olha; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose of the research is to examine social and psychological manifestations of professional identity crisis of labor emigrants. The methodological foundations are scientific approaches to determining an individual’s social and personal identity; the statement about labor migration as a manifestation of an individual’s social mobility; the social and psychological concept of labor migration, determined by identity crisis of individuals in the major areas of their self-realization – personal, professional and family relationships. The study establishes that changes in professional identity of emigrants occur during the period of being in different social and cultural conditions; transition from identity crisis towards mature identity or mainly towards diffuse identity is less common. The research discovers that if a respondent’s (labor migrant’s) profession mastered in an educational institution in Ukraine corresponds to the character of work and the area of activity in the country of employment, it causes the development of mature professional identity. We maintain that professional identity is simultaneously a condition and consequence of successful professional selfrealization of a labor emigrant in a different social environment.